Development of an index based on fish, macroinvertebrates, phytoplankton, and physicochemical properties to assess urban aquatic ecosystems in Jinan, China. (29th September 2022) - Liu, Linfei; Xu, Zongxue; Yin, Xuwang; Li, Fulin; Wang, Mi
Abstract: Because of the rapid growth in urbanization over recent decades, urban aquatic ecosystems have been subjected to unprecedented threats and challenges. In this study, we visited 48 sites, of which 14 were reservoir sites, in water bodies in Jinan, China, on six occasions in May, August, and October of 2014 and 2015. We sampled fish, macroinvertebrates, and phytoplankton assemblages and physicochemical factors at each site. We used the richness and diversity of fish, macroinvertebrates, and phytoplankton to evaluate the condition of the aquatic ecosystems of the river sites. We also evaluated the water quality of the reservoir sites using the physicochemical factors of the State Environmental Protection Administration of China. We classified the results into five levels—excellent, good, moderate, poor, and bad—with the comprehensive evaluation index (CEI). More than 40% of the sampling sites were in either poor or bad condition. Nearly half of the excellent or good sites were in the south of Jinan. The CEI was significantly different between the reference and impaired sites; it was significantly and positively correlated with the qualitative habitat evaluation index and was significantly and negatively correlated with conductivity, total alkalinity, and ammonia nitrogen.